METACOGNITIVE LEARNING STRATEGIES IN ENGLISH LANGUAGE TEACHING & LEARNING - Rat Dwiyana Putra, I Dewa Gede (Yavana Bhasha : Journal of English Language Education, 2018)
Metacognitive learning strategies (MLS) have been proven to promote problem solving skills and enable students to achieve better in learning (Aurah, 2013; Magogwe, 2013). Researches on MLS have also been done to investigate its effect on students’ performance in various ELT skills, e.g. listening, reading, speaking and writing. Most of the researchers found that MLS plays a significant role in students’ learning those four skills. However, there is still lack of studies done in academic writing especially within the Indonesian EFL setting. Besides, a research which is done by controlling various variables, e.g. English proficiency, students’ self-efficacy (self-regulatory factors), modes of writing (paper-based & internet based), etc. is required to give a clearer picture about the role of MLS in EFL academic writing. Keywords: metacognitive learning strategies, academic writing